2019
DOI: 10.1128/jvi.01832-18
|View full text |Cite
|
Sign up to set email alerts
|

HIV Subtype and Nef-Mediated Immune Evasion Function Correlate with Viral Reservoir Size in Early-Treated Individuals

Abstract: The HIV accessory protein Nef modulates key immune evasion and pathogenic functions, and its encoding gene region exhibits high sequence diversity. Given the recent identification of early HIV-specific adaptive immune responses as novel correlates of HIV reservoir size, we hypothesized that viral factors that facilitate the evasion of such responses—namely, Nef genetic and functional diversity—might also influence reservoir establishment and/or persistence. We isolated baseline plasma HIV RNA-derivednefclones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 81 publications
1
39
0
Order By: Relevance
“…As described above, Nef prevents cell-surface display of MHC-I complexes with HIV-1 antigenic peptides on infected cells, allowing escape from cytotoxic T lymphocytes. In this way, Nef inhibits clearance of the virus and may contribute to establishment and maintenance of the persistent viral reservoir (104). Mujib et al (102) showed that the direct acting Nef inhibitor B9, as well as several firstgeneration B9 analogs (103), restored MHC-I to the surface of HIV-infected CD4 T cells.…”
Section: Harnessing Kinase Activation By Nef For Anti-retroviral Drugmentioning
confidence: 99%
“…As described above, Nef prevents cell-surface display of MHC-I complexes with HIV-1 antigenic peptides on infected cells, allowing escape from cytotoxic T lymphocytes. In this way, Nef inhibits clearance of the virus and may contribute to establishment and maintenance of the persistent viral reservoir (104). Mujib et al (102) showed that the direct acting Nef inhibitor B9, as well as several firstgeneration B9 analogs (103), restored MHC-I to the surface of HIV-infected CD4 T cells.…”
Section: Harnessing Kinase Activation By Nef For Anti-retroviral Drugmentioning
confidence: 99%
“…While the major genetic determinants of Nef function are genetically separable [55][56][57], previous studies of natural nef sequences have demonstrated modest correlations between certain Nef activities [33,35,46,47], suggesting the presence of secondary or shared genetic determinants. Consistent with this, Nefmediated CD4 and HLA downregulation functions of the 50 studied clones correlated weakly (Spearman R = 0.35; p = 0.013), as did Nef-mediated CD4 and SERINC5 downregulation functions (Spearman R = 0.24; p = 0.047) (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…Nef amplicons were cloned into a modified pSELECT-GFPzeo vector containing AscI and SacII restriction sites within its multiple cloning site [47]. As described in [47], nef amplicons were digested with AscI and SacII, ligated into cut pSELECT-GFPzeo (T4 ligase; Thermo Fisher ® ), and transformed into chemically competent E. coli (E. cloni 10G DUOs; Lucigen). Plasmid DNA from a minimum of three colonies per transformation was isolated, purified (Thermo Fisher ® OMEGA EZNA plasmid minikit) and re-sequenced to confirm identity.…”
Section: Hiv Rna Extraction and Single-genome Amplification Of Nefmentioning
confidence: 99%
See 2 more Smart Citations